Heterogeneity of preferences and breeders’ willingness to pay for improved livestock system in Benin, West Africa - ZANOU, Murielle Aménia Monsoyi; ZANNOU, Afio; AOUDJI, AUGUSTIN KOSSI NOUNAGNON; HOUINATO, MARCEL ROMUALD BENJAMIN; Dossa, Luc Hippolyte (My University, 2023)
The productivity of livestock, including small ruminants, in Benin, is very low, and their management practices in terms of feeding, health and reproduction do not ensure their optimal production. This research aimed to assess the willingness of sheep and goat keepers to pay for an improved breeding system. Data collection from 118 sheep and 375 goat breeders selected in six agroecological zones of Benin was undertaken using the choice experiments. The mixed logit model revealed heterogeneity in the preferences of small ruminant keepers for breeds, feeding practices, health treatments and reproductive control. This heterogeneity of preferences was confirmed by the latent class logit model results, which revealed the existence of four classes of sheep breeders and three classes of goat breeders. Irrespective of species, small ruminant breeders were generally willing to use herbal medicine or combine it with modern veterinary medicine and adopt Sahelian breeds or crossbreeds (Sahelian x Djallonke). They were not willing to adapt neither zero grazing nor controlled reproduction. The combination of the coefficient estimates of the latent class logit model and the determinants of class membership showed that herders in southern Benin with small and monospecific herds were the most willing to introduce changes in their breeding system.
Keywords: Grazing; Supplementation; Phytotherapy; Sheep; Goats; Latent class logit; Mixed logit